PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Yahya Ayyasy; Dul Muid (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate social responsibility (CSR) performance on tax aggressiveness. The purpose of this study is to provide empirical evidence about the effect of overall CSR performance and each dimension on tax aggressiveness. The independent variable of this research is CSR performance, the dependent variable is tax aggressiveness, and the control variable is leverage, capital intensity, and profitability. CSR performance is measured through CSR disclosure with GRI G4 indicators. Leverage is measured by total debt divided by total assets. Capital intensity is measured by total fixed assets divided by total assets. Profitability is measured by Return on Assets (ROA). Tax aggressiveness is measured by the current effective tax rate (CuETR).The population in this study were 471 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample was selected by purposive sampling method and obtained 102 manufacturing companies that meet the criteria. Data were analyzed using multiple regression analysis model.The results of the study indicate that the overall CSR performance as well as on each dimension has no effect on tax aggressiveness. Based on the results of the study, it can be concluded that the tax aggressiveness decision is not influenced by his attitude towards the implementation of CSR.